A replication analysis of Laffitte and Toubal (2022) - Ipek Tastan; Kangyu Qiu; Tazia Khushboo; Leonard Goff (Institute for Replication (I4R), 2023)
We perform a robustness replication analysis of Laffitte and Toubal (2022), which considers how multinational corporations shift profit to "tax havens", jurisdictions where they face lower tax burdens. We find that the main results of Laffitte and Toubal (2022), are fairly robust to alternative versions of three important researcher choices: i) the definition of tax havens; ii) the use of a continuous measure of tax-friendliness rather than a binary classification of tax havens; and iii) a sample that omits two small but "extreme" tax havens: Bermuda and Barbados. In all cases, results remain of the same sign and retain statistical significance, though the magnitudes are somewhat attenuated in our robustness exercises.
Keywords: 330